2000
DOI: 10.1016/s0022-5347(05)67763-4
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Treatment May Harm the Germ Cells in 1 to 3-Year-Old Boys With Cryptorchidism

Abstract: In 1 to 3-year-old boys with cryptorchidism gonadotropin releasing hormone or HCG given for testicular descent may suppress the number of germ cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
2
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(44 citation statements)
references
References 18 publications
2
38
2
2
Order By: Relevance
“…In the first week hCG stimulation principally increases the mean weight of testes probably mediated by testosterone increase. In this period gonadotropin and testosterone are physiologically suppressed, thereby the impact of early hCG treatment is important [9]. In our study, in the hCG treated rats it has been observed a poor differentiation of the seminiferous epithelium, with high Leydig cell evidence and increased intertubular eosinophilic material.…”
Section: Discussionsupporting
confidence: 44%
See 2 more Smart Citations
“…In the first week hCG stimulation principally increases the mean weight of testes probably mediated by testosterone increase. In this period gonadotropin and testosterone are physiologically suppressed, thereby the impact of early hCG treatment is important [9]. In our study, in the hCG treated rats it has been observed a poor differentiation of the seminiferous epithelium, with high Leydig cell evidence and increased intertubular eosinophilic material.…”
Section: Discussionsupporting
confidence: 44%
“…Nevertheless its use in the management of cryptorchidism has been debated and potential harmful effects of hormonal therapy on the testis including apoptosis, inflammation and reduced number of germ cells continue to be explored [21]. Cortes and Thorup demonstrated that in one to three year boys with cryptorchidism HCG treatment may be hazardous to germ cells, therefore, they cannot be recommended [9]. Therefore considering the efficacy and the possible side effects of the hormonal treatment, the general use of hCG and GnRH in the treatment of cryptorchidism cannot be further recommended [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by Hadziselimovic et al, in which the effect of LHRH nasal spray on testicular descent was analysed, neither a stimulatory effect nor an inhibitory effect on the number of germ cells was seen (Hadziselimovic, 1980). This in contrast to Cortes et al, who found a negative effect on germ cells in 1-3-year-old boys with cryptorchidism after gonadotropin releasing hormone (GnRH) (Cortes, 2000). They hypothesized that these young boys may be sensitive for exogenous GnRH stimulation resulting in increased FSH, LH, and testosterone, which may have a negative impact on germ cells.…”
Section: Discussionmentioning
confidence: 93%
“…However, adverse effects of the hCG on testicular histology have been studied and demonstrated in many other clinical and experimental studies, some evidencing little benefit in the hormonal treatment of cryptorchidism and even deleterious effects 3,[11][12][13]17,18,25,26 .…”
Section: Discussionmentioning
confidence: 99%